Adaptive E-Learning: A systematic review of interactive and flexible learning aligned with student styles - Hastuti, Puji; Rahmawati, Ulfa Emi; Sakkinah, Intan Sulistyaningrum; Pratama, Raditya Arief; Hasanah, Qonitatul; Yunita, Tria; Wulandari, Laila (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
The development of digital technology and the popularity of the internet have made e-learning an increasingly popular learning method to support the dissemination of knowledge in interactive e-learning systems. However, currently, multimedia content-based e-learning systems are still under-explored, and most e-learning system models are not yet adaptive. On the other hand, each student has a different learning style when interacting with the content presented to them. The challenges faced if adaptive e-learning is not implemented properly can lead to poor learning outcomes. In this study, a systematic literature review was conducted with the PRISMA framework to study adaptive e-learning. From this study, 6 potential literatures were obtained from 193 literatures in the initial search regarding the implementation of adaptive e-learning systems that can answer global challenges in the future. The main finding of this study is that adaptive e-learning is able to overcome educational gaps in the future because students are increasingly dependent on digital learning systems worldwide. Ease of internet access plays a major role in the emergence of a lifelong learning system that can support students' learning styles. The results of this study can be the basis for further research in detecting students' learning styles as a basis for developing learning materials to support distance learning.